CENSURA FRANQUISTA D'UNA ANOTACIÓ DE DIETARI DE JOAN FUSTER. (June 2015) - TRILL, XAVIER FERRÉ
Abstract : The article presents an unpublished text by Joan Fuster Ortells, originally written to appear in the censored volume Dues visions . The reflection, not authorized by the censor – "Per a l'anàlisi del nacionalisme", i.e. "For an Analysis of Nationalism" – provides a critical view of Spanish nationalism and of the nation to be legitimized. The novelty of the reflection consists in overcoming the idea of regeneration, characteristic of certain Hispanic elites and denouncing the unionist attitude of Castilian-Spanish politicians and thinkers, as a common trait of progressive, republican, or (philo)fascist visions. The exposition includes the discussion of the essay as an expressive resource – or channel – of ideological literature. Taking the censored text as a starting point, the paper focuses on the social function of the intellectual.